Impact of educational intervention for correct inhaler technique on the quality of life of children with asthma - Konević, Slavica; Djonović, Nela; Djurić, Dušan; Marković-Denić, Ljiljana; Vasić, Dobrila; Martinović, Jelena (Vojnosanitetski pregled, 2021)
Background/Aim. Asthma is the most common chronic disease in children and adolescents and has shown an apparent increase in incidence in recent years. The first purpose of the study was to evaluate the influence of education about proper use of inhalers on quality of life in children with asthma. Secondly, we aimed to understand which aspects of quality of life in children with asthma can be significantly improved after education and to identify factors that may affect the level of that improvement. Methods. In this prospective, before-and-after interventional study, a total of 147 children with asthma were enrolled. The Pediatric Asthma Quality of Life Questionnaire (PAQLQ) was used to measure the functional problems that are most troublesome to children with asthma. We used the Asthma Control Test (ACT), based on a series of question about symptoms and daily functioning, to identify patients with poorly controlled asthma. Forced expiratory volume in one second (FEV1) and peak expiratory flow (PEF) were also determined. Trained educators estimated patients’ inhaler technique and collected questionnaire information. Results. Multivariate analysis of covariance indicated significant differences between PAQLQ and ACT scores which all were significantly higher after education about proper use of inhalers (p
Keywords: asthma; child; nebulizers and vaporizers; quality of life; education, medical; respiratory function tests